MEKANISME REKSADANA SYARIAH MELALUI APLIKASI BIBIT PERSPEKTIF AKAD WAKALAH BIL UJRAH - Muhammad Irkham Firdaus (UIN Siber Syekh Nurjati Cirebon, 2022)
Investment is one of the muamalah activities that is highly recommended in Islam, so platforms and applications that support investment activities are starting to appear, such as the Seed application. The Bibit application is an application that provides mutual funds and helps new investors to start investing. This application also provides a choice of sharia mutual funds, in which there are several sharia investment startups. However, in-depth research is needed on the mechanism of sharia mutual funds through the Seed application. This study aims to analyze the mechanism of Sharia mutual funds through the Seed Application with the wakalah bil ujrah contract. This type of research is field research and uses a qualitative descriptive approach. The results of the analysis of the wakalah bil ujrah contract on the mechanism of sharia mutual funds through the Bibit application concluded that the mechanism of sharia mutual funds through the Bibit application was not by the wakalah bil ujrah contract, because there were elements of taqshir and tahaddi, namely in providing information about past performance which determines the stimulation of future mutual fund values. now does not correspond to reality.Keywords: Sharia Mutual Funds, Bibit, Wakalah bil Ujrah